Analysis methodology for the strategies of educational programs in the system of additional professional education as a component of adaptive marketing - Ольга Харитонова (Вестник Пермского университета: Серия Экономика)
Introduction. Current context for the new regions of the Russian Federation (Lugansk People’s Republic, Donetsk People’s Republic, Zaporizhia and Kherson regions) demands radically new adaptive procedures for educational organizations to comply with the legislation of the Russian Federation. Academic studies do not refer to the internal component of the organization and the dynamic requests for appropriate educational programs from the target audience, in particular in the system of additional professional education. It is important for an educational organization to analyze current trends and develop recommendations for designing a flexible marketing model that responds to changes in demand, the competitive environment, and technological innovations. Purpose. The study demonstrates the key stages of analysis for the strategies applied to the educational programs in the system of additional professional education as the basis of adaptive marketing. Materials and Methods. The author used the methods of analysis, structuring, deduction, and mathematical modeling. The study referred to the materials of the Institute of Additional Professional Education and Distance Learning in Lugansk State University named after Vladimir Dahl. Results. The paper describes the algorithm of adaptive marketing applied to the educational programs in the system of additional professional education. Then, it looks at the analysis methodology stages for the educational programs in additional professional education. The paper gives the guidelines which could be used to define the tools for marketing educational services in the context of growth, stability, and reduction strategies. Conclusions. The author concludes that the intensity of the use of marketing tools reflects how far a higher education organization is ready to implement an adaptive marketing strategy, use modern competitive methods, and focus on achieving leading positions in a selected market segment or in the market as a whole. The prospects for further research come down to the development of a mathematical model for finding a balance between the costs of promoting educational programs and the costs of their implementation.